Eocene-Oligocene Climatic and Biotic Evolution - Donald R. Prothero, William A. Berggren (Princeton University Press, 2014)
The transition from the Eocene to the Oligocene Epochs was the most significant event in earth history since the extinction of dinosaurs. From the warm, equable climates of the Eocene, the earth underwent significant changes. Global temperature cooled more than any time since the Mesozoic, and the first Antarctic ice sheets appeared. There were major extinctions in both plants and animals on the land and in the oceans. By the Oligocene, the earth had a much cooler, more temperate climate, with a much lower diversity of organisms. In essence, the Eocene-Oligocene transition was the change from the "greenhouse" world of the Cretaceous and early Cenozoic to the glaciated world of today. This critical period of earth history has always fascinated scientists, but the recent interest in mass extinctions has increased the need to understand Eocene-Oligocene extinctions. Some have suggested that the Eocene-Oligocene extinctions were part of a periodic cycle that was also responsible for the Cretaceous-Tertiary extinctions. To test such hypotheses, there must be detailed studies of climatic information and organisms buried in Eocene-Oligocene sediments. Over the last decade, many such detailed studies have been undertaken, but very little of the information has been published. In marine geology, studies of the oceans around Antarctica have provided critical new evidence about the timing of Antarctic glaciation, and the oceanographic changes in the Southern Hemisphere. In terrestrial sections, new techniques of magnetostratigraphy and 4 ( Î† Î“ / 3 9 Î‘ Î“ dating have revolutionized our correlation of terrestrial sections, and the fossils contained within them. To specialists, this unpublished information was known by informal networks and by word of mouth. There was little communication between specialties, nor publication of these data for the rest of the world to see. For this reason, we thought that the best forum for such communication was an informal workshop. On August 1-5,1989, we held a Penrose Conference on this subject in Rapid City, South Dakota. During that meeting, paleontologists and stratigraphers of both the marine and terrestrial persuasions were able to meet and exchange ideas. The meeting was extraordinarily fruitful, and it soon became apparent that an important synthesis was emerging. Consequently, another meeting was held, this time as a Theme Session at the Annual Meeting of the Geological Society of America in St. Louis, Missouri on November 6, 1989. After this theme session, we decided to organize the contributors and publish their research. As the project grew, we learned of other scientists who had important information to contribute. Eventually, we were able to find authors representing nearly every major group of organisms in the ocean (from coccoliths, dinoflagellates, diatoms, foraminiferans, to molluscs, echinoids, and even whales) and on land (from soils, pollen, and plants, to land snails, reptiles, and land mammals). Since the effects were global, we have studies from both Southern and Northern Hemisphere oceans, and of land plants and animals in North America, Europe, Asia, and Africa. Besides the biological evidence, this book also includes evidence from seismology, stable isotopes, and sedimentology. There are also chapters on computer modeling of this critical period in climate history. Finally, the radical changes in the late Paleogene time scale necessitated several chapters on the new chronology of the Eocene and Oligocene. In addition to the overviews of the marine and terrestrial timescales, there are several papers on critical new evidence for these correlations, particularly in North American terrestrial sections. Since the timing of events is critical to the discussion, these chapters open the book. From the papers in this book, it is clear that the Eocene-Oligocene extinctions were much more complex than they are usually portrayed. Rather than a single abrupt "Terminal Eocene Event," there appear to be several events, the most of important of which occurred at the end of the middle Eocene. Although some of this complex story is summarized in the overview chapter, it is clear that we are just beginning to understand this critical and fascinating period of earth history.